2014
DOI: 10.1016/j.seizure.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic non-epileptic seizures in Iran

Abstract: Psychogenic non-epileptic seizures are relatively common at epilepsy clinics. It appears that an Islamic lifestyle (in Iran) has little influence on the clinical characteristics and manifestations of PNES, as we observed similar results as in most previous studies from other cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 18 publications
1
28
1
6
Order By: Relevance
“…In a previous study [6], we observed that different religion and culture in Iran do not affect the manifestations and most associated factors of PNES significantly (compared with those from the Western studies). This observation implies cross-cultural similarities in the clinical expression of PNES [6]. To the best of our knowledge, no study has ever investigated the association of education and PNES.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In a previous study [6], we observed that different religion and culture in Iran do not affect the manifestations and most associated factors of PNES significantly (compared with those from the Western studies). This observation implies cross-cultural similarities in the clinical expression of PNES [6]. To the best of our knowledge, no study has ever investigated the association of education and PNES.…”
Section: Introductionmentioning
confidence: 64%
“…With respect to the higher reported rate of sexual abuse in those with a higher education, we can contemplate two possible explanations. Extramarital sex is forbidden by law and religion in Iran and people, especially those who are not aware of their rights (such as illiterate people), might deny being sexually abused due to family considerations and fear of the consequences [6]. On the other hand, people with higher education may more openly talk about their conflicts and problems.…”
Section: Discussionmentioning
confidence: 99%
“…Psychogenic non-epileptic seizures (PNES) are relatively common occurrences in epilepsy centers 1 . However, PNES is a unique condition in that it is largely defined in terms of what it is not rather than what it is.…”
Section: Introductionmentioning
confidence: 99%
“…Psychogenic nonepileptic seizures (PNES) are relatively common occurrences in epilepsy centers [1,2]. These seizures consist of paroxysmal changes in responsiveness, movements, or behavior that resemble epileptic seizures, but lack a neurobiological origin similar to epileptic seizures and are not associated with electrophysiological epileptic changes [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…These seizures consist of paroxysmal changes in responsiveness, movements, or behavior that resemble epileptic seizures, but lack a neurobiological origin similar to epileptic seizures and are not associated with electrophysiological epileptic changes [1][2][3][4][5]. The incidence of PNES was estimated to be 1.4-4.9/100,000/year and the prevalence is calculated to be between 2 and 33 per 100,000, making it a significant psycho-neurological condition [2].…”
Section: Introductionmentioning
confidence: 99%